Economic Analysis of Energy Transmission for Energy Island Based on Deep-Sea Offshore Wind Farms - Zhongqi LIU; Yao LIU; Jinming HOU (Zhongguo dianli)
Deep-sea wind power has the advantages of rich resources, high utilization hours, and no occupation of land onshore, which is of great significance for promoting the realization of the "double carbon" goal. The offshore energy island with deep-sea wind power as the core can, through the integrated development model of "offshore wind power +", improve the comprehensive utilization rate of sea areas, enhance overall efficiency, and reduce development costs. Construction of the offshore energy island involves energy development technologies such as floating offshore wind power, energy comprehensive utilization technologies such as AWE, energy transmission technologies such as VSC-HVDC transmission and hydrogen pipeline transmission. This paper first introduces the overall composition of the energy island with the deep-sea wind power as the core, and then analyzes the transmission technologies applicable to large-scale energy transmission of the energy island. The cost of the energy island with 1000 MW floating offshore wind power through VSC-HVDC power transmission and the cost of hydrogen transmission through pipeline are calculated respectively, and the power transmission cost is compared with the cost of hydrogen transport. As the comparative analysis indicates, both the VSC-HVDC technology and the hydrogen pipeline transmission technology can be used as the energy transmission solutions for the offshore energy island. An innovative research is carried out on the economics of energy delivery for energy island. According to calculations, in 2023, 2030, and 2050, when the transmission distance is 100 km to 200 km, the economic performance of the VSC-HVDC solution is better than that of the hydrogen transmission solution. The cost and absorption capacity of the landing area need to be comprehensively considered before choosing the power transmission solution or the hydrogen transmission solution. It is predicted that in 2050, the comprehensive cost of different proportions of mixed power and hydrogen transmission for a distance of 100 km to 200 km offshore is between 0.18 yuan/kW·h and 0.27 yuan/kW·h, which is competitive compared with the cost of power transmission from new energy bases in the western and northern regions to the eastern region.